Magic Tree House, Merlin Mission: High Time for Heroes - Book 51 (23) - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2014)
"Jack and Annie are magically transported to mid-1800's Thebes where they are saved from a dangerous accident by Florence Nightingale!"--
Keywords: Nightingale, Florence, -- 1820-1910 -- Juvenile fiction; Nightingale, Florence, -- 1820-1910 -- Fiction; Time travel -- Juvenile fiction; Magicians -- Juvenile fiction; Nurses -- Juvenile fiction; Tree houses -- Juvenile fiction; Time travel -- Fiction; Magicians -- Fiction; Nurses -- Fiction; Tree houses -- Fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Historical / General; JUVENILE FICTION / Fantasy & Magic; Thebes (Egypt : Extinct city) -- Juvenile fiction; Thebes (Egypt : Extinct city) -- Fiction